Bridging the Gap—Building Surgical Subspecialty Telemedicine Clinics in the Rural Setting. Issue 2 (13th March 2022) - Ferari, Christopher; Mitchell, Katharina; Crigger, Chad; Zupper, Shirley; Wildasin, Amy; Ost, Michael; Hendricks, Brian; Al-Omar, Osama
Abstract: Introduction: Pediatric urology is a much-needed subspecialty with a breadth of complex disorders that can often prove challenging to diagnose and manage. Exacerbating this need is the minimal exposure medical trainees receive to pediatric urology. Pediatric urology arrived in West Virginia in 1983 but the subspecialty has been inconsistently represented since then. Currently there are 2 fellowship-trained pediatric urologists in the state of West Virginia, which has an area of approximately 24, 038 square miles. We review our experience with the use of telemedicine in providing outreach to the wider parts of our medically underserved state and ultimately evaluate its efficacy from a patient-centric cost analysis and diagnosis concordance perspective. We hypothesized that the use of telemedicine would be cost and time-effective for patients in our rural state. Methods: We retrospectively reviewed our series of patients presenting from outside telemedicine "referral centers" in Martinsburg, Parkersburg and Wheeling for pediatric urological consultation. We evaluated reason for consultation, geographic driving distance, drive time and travel cost saved from telemedicine consultation. Results: A total of 92 patients presented to outside designated telemedicine centers from August 2018 to April 2020. The mean driving time saved utilizing telemedicine consultation was 4 hours and 46 minutes, and mean driving distance saved was 299.8 miles. Travel costs saved in terms of fuel averaged $173.88 per patient. The most common reason for consultation was undescended testis, followed by recurrent urinary tract infection and nocturnal enuresis. Of the 23 patients who required surgery, only 2 (8.7%) had an initial diagnosis that was not concordant with their operating room examination. Conclusions: While modest, our data indicate a modern solution to a historical need in our state. Our high diagnosis concordance rate (91.3%) shows that a well-trained advanced practice provider can adequately perform an operative evaluation via telemedicine.